Express and portable label-free DNA detection and recognition with SERS platform based on functional Au grating; Applied Surface Science; Vol. 470 - Guselnikova O. A. Olga Andreevna; Postnikov P. S. Pavel Sergeevich; Pershina A. G. Aleksandra Gennadievna; Svorcik V. Vaclav; Lyutakov O. Oleksy (2019, 2019)
Title screen